2015
DOI: 10.1016/j.ahj.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

A reappraisal of loop diuretic choice in heart failure patients

Abstract: The health and economic burden of heart failure is significant, and continues to grow each year. Loop diuretics are an integral part of symptom management in heart failure. Furosemide is used disproportionately compared to other loop diuretics and there is currently no guidance for physicians regarding which agent to choose. However, there exist pharmacologic differences as well as other mechanistic differences that appear to favor torsemide use over furosemide. Compared to furosemide, torsemide improves surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 66 publications
1
67
0
11
Order By: Relevance
“…18 A systematic analysis of torsemide versus furosemide comparative effectiveness suggested that torsemide reduced heart failure readmissions, 19 but available data are limited and the question is well-suited for definitive clinical trials. 20 …”
Section: Introductionmentioning
confidence: 99%
“…18 A systematic analysis of torsemide versus furosemide comparative effectiveness suggested that torsemide reduced heart failure readmissions, 19 but available data are limited and the question is well-suited for definitive clinical trials. 20 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that torsemide may be associated with better outcomes than furosemide in chronic HF patients 22 . A small (N=234) open-label, randomized study by Murray et al compared chronic HF with reduced EF patients receiving torsemide vs. furosemide 5 .…”
Section: Discussionmentioning
confidence: 98%
“…They further reported the ability of torsemide to correct both lysyl oxidase overexpression and enhanced collagen cross-linking leading to normalization of LV chamber stiffness in patients with heart failure (López et al, 2009). This was supported by preclinical data showing torsemide's effect on RAAS inhibition including decreasing aldosterone secretion, inhibiting aldosterone receptor and Ang II effects (Buggey et al, 2015). However, in the TORAFIC study, a multi-center study of 155 hypertensive patients with chronic heart failure randomized to torsemide or furosemide, investigators did not find significant differences between the two groups in changes of PICP (Group, 2011).…”
Section: Anti-fibrotic Therapies On Cardiac Fibrosis In Clinical Trialsmentioning
confidence: 81%